Deep Neuromuscular Block to Optimize Surgical Space Conditions During Laparoscopic Surgery: A Systematic Review and Meta-analysis. Issue 5 (October 2017) - Bruintjes, M. H.; van Helden, E. V.; Braat, A. E.; Dahan, A.; Scheffer, G. J.; van Laarhoven, C. J.; Warlé, M. C.
Abstract : (Abstracted from Br J Anaesth, 118(6):834–842, 2017) Lowering the elevated intra-abdominal pressure during pneumoperitoneum created in laparoscopic procedures can impair the quality of the surgical field and increase the risk of intraoperative complications. Deep neuromuscular block (NMB) has been known to improve surgical conditions in laparoscopic procedures; however, the routine use of NMB is still debatable.